2021
DOI: 10.1002/aenm.202102819
|View full text |Cite
|
Sign up to set email alerts
|

A Tandem Electrocatalysis of Sulfur Reduction by Bimetal 2D MOFs

Abstract: polysulfide by the host materials are conventional approaches to tackle the dissolution problem, [3,4] nonetheless, these could only partially alleviate the shuttle effect due to low fraction of host material in the electrode. Using "flooded" electrolyte could dilute the polysulfide solution thus somehow improves the redox kinetics due to enhanced mass/charge transfer, although it inevitably decreases the actual energy density of the battery. [1] Alternatively, recently established proactive electrocatalysis s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(56 citation statements)
references
References 50 publications
1
55
0
Order By: Relevance
“…For instance, the 2D integrated bimetal CoNi‐MOF, where the Ni and Co sites were connected via an O bridge (Figure 8i). [ 140 ] The photon energy of Co and Ni in CoNi‐MOF was changed compared to that in single‐metal MOFs, confirming the charge transfer between the Ni–O–Co bridge (Figure 8j). This electron redistribution endowed the unoccupied 3 d e g state of Ni or Co, which would enhance the electrocatalytic activities for polysulfide conversion.…”
Section: Modulating Bond Interactions Of Psrcs For Advanced Msbsmentioning
confidence: 75%
See 1 more Smart Citation
“…For instance, the 2D integrated bimetal CoNi‐MOF, where the Ni and Co sites were connected via an O bridge (Figure 8i). [ 140 ] The photon energy of Co and Ni in CoNi‐MOF was changed compared to that in single‐metal MOFs, confirming the charge transfer between the Ni–O–Co bridge (Figure 8j). This electron redistribution endowed the unoccupied 3 d e g state of Ni or Co, which would enhance the electrocatalytic activities for polysulfide conversion.…”
Section: Modulating Bond Interactions Of Psrcs For Advanced Msbsmentioning
confidence: 75%
“…i-k) The electron transfer between Ni and Co in the CoNi-MOF and corresponding influence on the activation energy barrier for polysulfide catalytic conversion. Reproduced with permission [140]. Copyright 2021, Wiley-VCH.…”
mentioning
confidence: 99%
“…Peaks 2.30 V and 2.05 V are related to the reduction S 8 to Li 2 S 4 and following conversion from Li 2 S 4 to Li 2 S, and anodic peaks at 2.31 and 2.4 V are attributed to the oxidation of Li 2 S to Li 2 S 4 and Li 2 S 4 to S 8 , which suggests that the Co and Fe atom catalysts can promote the long-chain and short-chain polysulfide conversion reaction. 65,66 While anchoring Co and Fe atoms on NC, positive shifts in the cathodic peaks and negative shifts in the anodic peaks were generated, which illustrates the enhanced catalytic activity of the S@CoFe-NC on the conversion reaction of the sulfide species. When the symmetric cells comprising of two same NC, Co-NC, Fe-NC and CoFe-NC electrodes using 0.5 M Li 2 S 6 -containing electrolyte were employed, a similar result could be revealed, that is, fast reaction kinetics and high redox charge storage capacity of the CoFe-NC electrode (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…Meng et al synthesized single-metal and bimetal MOFs based on Ni and Co ions by controlling the ratios between BDC ligands and Ni or Co ions. 184 The obtained CoNi-MOF displays a flexible morphology of 2D nanosheets, as depicted in the SEM images (Fig. 22a).…”
Section: D Metal-organic Framework (Mofs)mentioning
confidence: 85%
“…22a). 184 AFM imaging of the CoNi-MOF indicated that the nanosheets had a mean thickness of 4.6 nm (Fig. 22b).…”
Section: D Metal-organic Framework (Mofs)mentioning
confidence: 99%